Three-dimensional cubic ordered mesoporous carbon (CMK-8) as highly efficient stable Pd electro-catalyst support for formic acid oxidation - Maiyalagan, Thandavarayan (2013)
In this work, Pd nanoparticles were supported on two types of three-dimensional cubic highly ordered mesoporous carbon (CMK-8) by the sodium borohydride reduction method and the activity of the Pd/CMK-8 electro-catalysts towards formic acid oxidation was evaluated and compared with that of commercial Pd/C (E-TEK) catalyst. The catalysts were characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD), cyclic voltammetry, and chronoamperometry. Cyclic voltammetry revealed Pd/CMK-8 with larger pores as being the most electroactive with a mass specific activity (mA mgPd−1) of 486.4 that exceeded not only that of the Pd/C (E-TEK) (386.5 mA mgPd−1) but also that of recently reported Pd/CNT (200 mA mgPd−1), Pd/Graphene (210 mA mgPd−1) and Pd/Vulcan XC 72 (193 mA mgPd−1). As demonstrated with chronoamperometry, the larger pore Pd/CMK-8 also proved to be the most stable catalyst. This exceptional performance can be ascribed to the very high surface area and Ia3d symmetry that yields a relatively isotropic graphitized structure with a high conductivity. In addition, the open framework of the 3-D bicontinous channels and highly ordered mesopores allows for an advanced mass transfer characteristics. The results show that CMK-8 support would significantly improve the power output and stability of Pd-based electro-catalysts for formic acid oxidation.